Photophysical properties and estimation of ground and excited state dipole moments of 7-diethylamino and 7-diethylamino-4-methyl coumarin dyes from absorption and emission spectra - Husain, Mohd Mudassir; Sindhu, Rajeev; Tandon, Harmesh Chander (European Journal of Chemistry, 2012)
In the present work, the effect of solvents on absorption and fluorescence spectra and dipole moments (μg, μe) of 7-diethylamino coumarin (7DEAC) and 7-diethylamino-4-methyl coumarin (7DEA4MC) have been studied in different solvents of various polarity at room temperature. The solvents have been selected in a way to cover the full range of intermolecular interactions from non-polar hexane to strongly polar formamide. Using the methods of solvatochromism, the difference in the first excited singlet-state (μe) and ground state (μg) dipole moments was estimated from Lippert-Mataga, Bakhshiev, Kawski-Chamma-Viallet and McRae equations. The Onsager’s cavity radius of the probes has been calculated by AM1 and PM3 quantum chemical calculations and also by a direct relation. The change in dipole moment value (Δμ) was also calculated by using the variation of Stoke’s shift with microscopic solvent polarity parameter (ETN). The calculated dipole moments represent new results, as well as some of the solvatochromic results that were not studied earlier in such large number of solvents. It is observed that the values of excited singlet-state dipole moments are higher than the ground state ones in both the molecules, which shows that excited states are more polar than the ground states.